The phenomenon of illegal immigration and its relations with organized crime. : Trafficking in human beings in North African countries as a model - Tartag, Zakaria (Journal of Human Sciences, 2021)
The phenomenon of illegal immigration is a source of concern that threatens the sovereignty of all countries : exporters, receivers and transit countries, and weakens international relations. Migration results from economic, political, security, social and psychological factors. The dynamics of this phenomenon are influenced by geographical proximity. As North African countries are the gateway to Europe, they have had to pay their share of African migrants from the Sahel to Europe. The purpose of this article is to highlight the phenomenon of illegal immigration and its direct contribution to the spread of transnational organised crime. This is the crime of trafficking in human beings, a crime with universal resonance, because it has a vast geographical dimension, on the one hand, and it is both a crime threatening the national security and a crime against humanity, on the other hand.